Is the Success of Plant Invasions the Result of Rapid Adaptive Evolution in Seed Traits? Evidence from a Latitudinal Rainfall Gradient - Molina-Montenegro, Marco A.; Acuña-Rodríguez, Ian S.; Flores, Tomás S. M.; Hereme, Rasme; Lafon, Alejandra; Atala, Cristian; Torres-Díaz, Cristian (Frontiers in Plant Science, 2018)
It has been widely suggested that invasion success along broad environmental gradients may be partially due to phenotypic plasticity, but rapid evolution could also be a relevant factor for invasions. Seed traits such as the endosperm to seed coat proportion (ESCP) are variable along gradients and can be heritable, thus they have the potential to evolve by means of natural selection. Utilizing reciprocal transplant experiments and heritability measurements of thickness of seed traits and ESCP in a second generation (F2) of Taraxacum officinale sampled from a latitudinal gradient in Chile, we evaluated the adaptive value of several seed traits and their potential for evolution in this species. In addition, we characterized the genetic variability of the sampled individuals with amplified fragment length polymorphism (AFLP) markers, analyzing its spatial distribution and population structure. Overall, thickness of seed coat and ESCP increased with latitude, indicating that individuals of T. officinale from northern populations have a thicker seed coat than those from southern populations. Germination increased with greater addition of water and seeds from southern localities germinated significantly more than those from the north. In addition, reciprocal transplants showed significant differences in survival percentage and biomass accumulation among individuals from different localities and moreover, the expression of ESCP between maternal plants and their offspring was highly correlated, suggesting an adaptive evolution in T. officinale. On the other hand, significant genetic differences were observed, however under the extreme climatic conditions experienced by northern individuals, these differences tend to disappear. Our results showed that climatic conditions affect both, the ESCP and the genetic variability in the invasive T. officinale, suggesting that this seed trait is indicative of adaptive evolution by natural selection. Thus, invasion along broad geographical gradients in many cases may be the result of the presence of functional traits in invasive species with rapid adaptive capacity.